2012
DOI: 10.1016/j.jedc.2011.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Firm-network characteristics and economic robustness to natural disasters

Abstract: Cet article étudie la robustesse d'une économie régionale à un choc exogène tel qu'une catastrophe naturelle. Il est basé sur une modèle dynamique qui représente une économie régionale comme un réseau d'unités de production constitué à partir d'une table entrée sortie sectorielle. Les résultats suggèrent que les pertes de production liées aux catastrophes naturelles dépendent de l'hétérogénéité des pertes directes et de la structure du réseau économique. Deux indices agrégés la concentration et le regroupement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
113
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 33 publications
6
113
0
Order By: Relevance
“…Wenz and Levermann (2016) employed the model to study heat-stress induced production losses in the global supply network. They observed that in recent years the supply network has become more susceptible to loss propagation due to an enhanced interconnectivity of the economy, well in line with the findings of Henriet et al (2012).…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Wenz and Levermann (2016) employed the model to study heat-stress induced production losses in the global supply network. They observed that in recent years the supply network has become more susceptible to loss propagation due to an enhanced interconnectivity of the economy, well in line with the findings of Henriet et al (2012).…”
Section: Introductionsupporting
confidence: 73%
“…This model was successfully employed in several empirical disaster impact studies such as Hallegatte (2009), Ranger et al (2011), and Hallegatte et al (2011). Further, Henriet et al (2012) extended the model to study how the robustness of a firm network to micro-shocks depends on the structure of the network as well as the heterogeneity of direct losses. Moreover, the authors provided an algorithm to disaggregate sectoral I-O tables such that a firm network with realistic size distribution is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The Tohoku Pacific earthquake could thus be an illustration of the type of events the world will have to deal with in the future. Such a trend toward larger disasters translates into a strong and increasing need for crisis management and post-disaster support, through (1) forecasts and early warning to mitigate human losses (e.g., Subbiah et al, 2008;Hallegatte 2012); (2) rainy-day funds and insurance and reinsurance schemes to support reconstruction (e.g., Ghesquiere and Mahul, 2010;Jaffee et al, 2010;MichelKerjan, 2010); and (3) new international instruments for post-disaster support and solidarity (e.g., Linnerooth-Bayer et al 2009). Finally, the growing role of exceptional disasters, on which knowledge and data is the scarcest, call for decision-making processes that are able to cope with large uncertainty (Lempert and Collins, 2007;Paté-Cornell, 2012;Hallegatte et al, 2012).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Insurance and post-disaster support are often available in developed countries, and households and firms in risky areas do not pay the full cost of the risk, and may take more risk than what is socially optimal (e.g., Kaplow, 1991;Burby et al, 1991;Laffont, 1995). Also, Lall and Deichmann (2010), Hallegatte (2008) and Henriet et al (2012) show that risk mitigation has positive externalities and that private and social costs of disaster losses may differ, leading to inappropriate risk taking.…”
Section: Taking Into Account Biases In Risk Perceptionmentioning
confidence: 99%
“…These include large-scale models dealing with the indirect economic losses of natural hazards (Crowther et al, 2007;Hallegatte, 2008;Henriet et al, 2012), methods to evaluate damage caused by the disruption of transport, wastewater and electricity networks (Penning-Rowsell et al, 2005), damage through the loss of accessibility to a territory (Demoraes, 2009;Demoraes and D'Ercole, 2009), by the disruption of the water system (Hardy, 2009), and by the interruption of gas distribution (Bouchon, 2009). Regarding internal direct and indirect damage to infrastructures, few data and no 1 French National press information.…”
mentioning
confidence: 99%